2000 IEEE/SEMI Advanced Semiconductor Manufacturing Conference and Workshop. ASMC 2000 (Cat. No.00CH37072)
DOI: 10.1109/asmc.2000.902602
|View full text |Cite
|
Sign up to set email alerts
|

Residue removal after via-hole etching

Abstract: Using a combined microwave downstream plasma and low damage NE, we have successfully developed a dry process that removes both the photoresist and the remaining polymer residue after a via etch step.An ion assisted plasma process containing oxygen and fluorine was successfilly developed. It was found that the ion-assisted process converted the Ti, Si and their oxide containing residues to water-soluble compounds. Thus, a room temperature DI water rinse after the dry process removed the entire sidewall residue.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…For this reason, one of the most important aspects in the via hole cleaning process is the removal of this metallorganic polymer layer formed on the sidewalls and bottoms of via holes. 5 The cleaning process of the sidewall and bottom polymers of a via hole formed during RIE can be divided into three steps: ͑i͒ plasma dry ashing of the photoresist, ͑ii͒ wet cleaning of residual photoresist and polymer residues, and ͑iii͒ in situ Ar dry cleaning before upper metal sputtering. These post-RIE cleaning processes are ideally required to remove residual polymers completely before the metal gap filling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, one of the most important aspects in the via hole cleaning process is the removal of this metallorganic polymer layer formed on the sidewalls and bottoms of via holes. 5 The cleaning process of the sidewall and bottom polymers of a via hole formed during RIE can be divided into three steps: ͑i͒ plasma dry ashing of the photoresist, ͑ii͒ wet cleaning of residual photoresist and polymer residues, and ͑iii͒ in situ Ar dry cleaning before upper metal sputtering. These post-RIE cleaning processes are ideally required to remove residual polymers completely before the metal gap filling.…”
mentioning
confidence: 99%
“…Conventional removal of photoresist and RIE polymer residues was done using a two-step cleaning process which includes the ashing using an O 2 ͑or O 2 /N 2 ) plasma and the stripping using a hydroxylamine ͑HA͒-based chemical. 1,5 However, it was reported that the HA-based wet strip process did not completely remove the sidewall polymer formed in via holes with via etch-stopped on a TiN layer ͑VEST͒ structure. Therefore, in this study we investigated the effect of a post-RIE cleaning process using a non-HA-based stripper under various conditions to optimize the post-RIE residue removal.…”
mentioning
confidence: 99%